The Evolution of E-Learning Management Systems: An Ethical Approach - Silva, Nuno Sotero Alves da (2014)
The development of educational technologies is enhancing a distinctive feature of learning environments: the learner’s personalized environment. However, the current literature in e-learning seems to neglect an important discussion: will individuals (learners and lecturers) and organizations face an enhancement concerning ethical dilemmas due to this evolution? To promote this discussion, this paper builds on a consideration of e-learning definition and its ethical dilemmas, and human-centred learning concept and its dimensions, to examine the implications of integrating social and cultural contexts. By examining the evolution of e-learning management systems the argument progresses to a discussion of the relationships between pedagogy and ethics. By framing evidence at different scales, the authors critically reflect on the ethical dilemmas embedded in e-learning systems. The discussion concludes with advocating the adoption of an extension of “three P” mode of pedagogy to become the “P3E” model: personalization, participation, productivity, lecturer’s ethics, learner’s ethics, and organizational ethics